2012
DOI: 10.1016/j.jprot.2012.07.040
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic identification of quality factors for oocytes in the Pacific oyster Crassostrea gigas

Abstract: We used a 2-DE proteomic approach to identify abundant proteins linked to oocyte quality in the Pacific oyster Crassostrea gigas, an economically important bivalve. Oocyte quality of 14 females was estimated by recording fertilisation and early developmental success until D-larval stage under controlled conditions. Proteins that were differentially expressed between females showing high or low oocyte quality were identified by nano-liquid chromatography tandem mass spectrometry. Twelve up-accumulated spots ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 66 publications
3
44
0
Order By: Relevance
“…Total proteins were extracted and analyzed using 2D electrophoresis, and spots were quantified in Coomassie bluestained gels as in Corporeau et al (55). In-gel digestion was performed for excised spots based on their differential expression, as quantified using Progenesis SameSpots v1.5 software (Nonlinear Dynamics), followed by LC-MS/MS analyses (55).…”
Section: Methodsmentioning
confidence: 99%
“…Total proteins were extracted and analyzed using 2D electrophoresis, and spots were quantified in Coomassie bluestained gels as in Corporeau et al (55). In-gel digestion was performed for excised spots based on their differential expression, as quantified using Progenesis SameSpots v1.5 software (Nonlinear Dynamics), followed by LC-MS/MS analyses (55).…”
Section: Methodsmentioning
confidence: 99%
“…Recent advances in gamete signaling pathways revealed that AMPK is involved in the gamete quality of Sus scrofa [120]. A high individual variability of gamete quality was reported in C. gigas [121,122], and it would be interesting to test whether AMPK signaling could play a role in gamete quality in our model. Looking more deeply into the energy network described by the Spearman correlation coefficient matrix, we can say that network organization with gene clusters can be drawn for managing the energy during the energy spending period of C. gigas gametogenesis.…”
Section: Suggested Roles Of Creb Pi3k and Akt In Oyster Reproductionmentioning
confidence: 98%
“…Samples were stored at À80 C until being powderized in a Retsch MM 400 blender by grinding with liquid nitrogen. The powder obtained was stored at À80 C. Before use, samples were resuspended in 500 mL of lysis buffer [37]. The resuspended powder was then homogenized using Ultra-Turrax (Modele PRO 200) and centrifuged at 10 000 g for 45 min at 4 C. Enzymatic and protein assays were carried out on the resulting supernatant.…”
Section: Tissue Collection and Protein Extractionmentioning
confidence: 99%